PERSEPSI MASYARAKAT TERHADAP PENGOBATAN TRADISIONAL BERDASARKAN PENDIDIKAN DI KABUPATEN PURWAKARTA - Puspariki, Jenta; Suharti, Suharti (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2019)
Background: The use of chemical drugs for long periods can lead to new disease for many body organs damaged by chemical drugs. Aware of the danger, people are starting to reduce the use of chemical drugs and turn to traditional medicines. Although the use of traditional medicine has a lot of data but user education is still a bit of traditional medicine. Background information studied education because education can influence the perception held one perception to traditional medicine. Objective: To explore community perceptions of traditional medicine based education. Method: The study is a qualitative explanatory associative. His research interests Purwakarta Regency society as much as 137 people. Selection and sampling using conditional sampling method, which is analyzed by the scale Ridwan (2009). Retrieving data using questionnaires. Results: The group never attended (TPK) perception and interest strongly agree and agree to traditional medicine by 78.7%, 62.7% and at S1 S2 / S3 66%. TPK groups agree and strongly agree traditional medicine has the potential to be developed with a percentage of 81.9%, 70.3% S1 and S2 / S3 76.7%. TPK groups agree and strongly agree folk medicine cure enough to give evidence to the percentage of 67.4%, 51.8% S1 and S2 / S3 50%. TPK groups agree and strongly agree traditional treatment facilities are still modest at 80.4%, S1 agreed amounted to 50.6% and S2 / S3 are agreed by 50%.. Conclusion: For the perception and interest towards traditional medicine and traditional medicine shows potential for the development of a large percentage of the group TPK, then S2 / S3 then S1. Traditional treatment sufficient to provide evidence of healing and traditional medicine practices facilities showed a large percentage in the group of TPK, the next and last S1 S2 / S3.